Turf maintenance with gardena pushreel and rotational mowers - Kulin, Balázs; György, Attila; Zsigó, Gábor; Szemán, László (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The subject of the dissertation: research of the different cutting mechanism mowers. The different fertilizing technologies on the park type of lawn, wich is not or just sometimes irrigated. The aim of the experiment: Work with GARDENA lawn mowers on the land and examine what effect has on the grass. The effect of Gardena lawn mowers on the grass. The dissertation presents, the experiment with different types of SCOTT artificial fertilizers the influence of different cutting hight, and the spread of weeds in the turf. The growing energy and density difference in between the air and not air turf. The dissertation presents the different cutting hight makes different combination of botanical species, it supports by the measured informations. The green color of the turf is depending on the nutrition and the influencing time of SCOTT fertilizers. The AN lost earlier the effection for the color, but the long lasting fertilizer helps the green color look more aesthetic.
Keywords: lawn; reel mower; rotational mower; cutting hight; nutriton supply